2004
DOI: 10.1098/rsbl.2004.0210
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that insect herbivores are deterred by ant pheromones

Abstract: It is well documented that ants can protect plants against insect herbivores, but the underlying mechanisms remain almost undocumented. We propose and test the pheromone avoidance hypothesis-an indirect mechanism where insect herbivores are repelled not only by ants but also by ant pheromones. Herbivores subjected to ant predation will experience a selective advantage if they evolve mechanisms enabling them to avoid feeding within ant territories. Such a mechanism could be based on the ability to detect and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 8 publications
(14 reference statements)
2
72
0
Order By: Relevance
“…The presence of 14 ant species including O. smaragdina provided an insight into the importance of their presence on cashew trees with regard to the absence of major insect pests during the phenological cycle because damage symptoms were not reported in the cashew field (personal observation, second author; personal communication, cashew field owner). According to Offenberg et al (2004) interspecific pheromones of the ants may have repelled the cashew pests. Rickson & Rickson (1998) reported 8-11 species of ants including A. gracilipes, C.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of 14 ant species including O. smaragdina provided an insight into the importance of their presence on cashew trees with regard to the absence of major insect pests during the phenological cycle because damage symptoms were not reported in the cashew field (personal observation, second author; personal communication, cashew field owner). According to Offenberg et al (2004) interspecific pheromones of the ants may have repelled the cashew pests. Rickson & Rickson (1998) reported 8-11 species of ants including A. gracilipes, C.…”
Section: Discussionmentioning
confidence: 99%
“…The Search Rate of the African Weaver Ant in Cashew Introduction control agents in fruit trees, such as mango and cashew (Way & Khoo, 1992;Peng et al, 1999a;Offenberg et al, 2004;Peng & Christian, 2006;Dwomoh et al, 2009) Dwomoh et al (2009) showed that O. longinoda was as effective in protecting cashew against pest insects as insecticides such as l-cyhalothrin and cypermethrin + dimethoate. Several studies suggest that with appropriate management weaver ants can significantly increase fruit yield and reduce the use of pesticides (Van Mele, 2008).…”
mentioning
confidence: 99%
“…Some insects may also have the ability to detect the chemical signals associated with ants. For example, A. bipunctata beetles are able to adjust their behaviour in response to L. niger semiochemicals (Oliver et al, 2008), and Offenberg et al (2004) found that chrysomelid beetles (Rhyparida wallacei Baly) preferentially fed on leaves collected from trees absent of Oecophylla smaragdina …”
Section: Discussionmentioning
confidence: 99%
“…Gonsalves et al (2005) also found that predatory ants had a negative effect on termite activity, while non-predatory ants did not, suggesting that predation by ants may be an important disturbance factor in some ecosystems. In some cases, direct interactions with ants may not be required for them to influence other arthropods (Offenberg et al, 2004;Oliver et al, 2008). Artificially low Formica aquilonia Yarrow ant densities created by Laakso and Setala (2000) also resulted in increased activity of other predatory arthropods, which they described as a compensatory shift in the predatory invertebrate guild.…”
Section: a Biological Indicator Is A "Species Or Group O F Species mentioning
confidence: 99%
See 1 more Smart Citation